Pendekatan Hadis Normatif Dalam Peradaban Islam - Zaimuddin, Zaimuddin; Masruchan, Masruchan (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2022)
This paper is a description of the normative hadith approach which is the most dominant approach in understanding Islam and in the legal istinbat process. Unmitigated, this approach was built at the same time by two sciences, namely the science of hadith and the science of ushul fiqh, which must have also become the focus of studies of major Muslim figures such as Imam Syafii. This shows that the doctrine in Islam is not passive, but stimulates research, study, and gives birth to a very scientific understanding actively.